GIS and Remote Sensing Applications for Resource Mapping - Shrestha, HL (The Initiation, 2010)
Key words: Remote sensing; GIS; GPS; Resource mapping; Forest DOI: 10.3126/init.v1i0.2681 The Initiation Vol.1 2007 p.56-61